2020
DOI: 10.1021/acssuschemeng.0c05583
|View full text |Cite
|
Sign up to set email alerts
|

Improving Enzymatic Saccharification and Ethanol Production from Hardwood by Deacetylation and Steam Pretreatment: Insight into Mitigating Lignin Inhibition

Abstract: Lignin component in lignocellulosic biomass always adversely affects the efficiency of its enzymatic saccharification and subsequent bioethanol production. To mitigate the lignin inhibition, this work thoroughly evaluated the effectiveness of deacetylation and steam pretreatment for improved fermentable sugars and bioethanol production from hardwood as well as quantified the relative contribution of lignin toward physical blockage effect and unproductive adsorption effect on cellulose hydrolysis. It was found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(14 citation statements)
references
References 59 publications
1
13
0
Order By: Relevance
“…The negative effects of lignin on enzymatic hydrolysis have been comprehensively reviewed and discussed by many researchers. , We also confirmed the inhibition of lignin (milled bamboo lignin, MBL) to the enzymatic conversion (EC) of typical microcrystalline cellulose (Avicel) (Figure S3). Based on macroscopic adsorption experiments, numerous studies had found that competitive adsorption of cellulase with lignin was more superior to that with cellulose in a coexisting buffer system, which significantly reduced the amount of effective cellulase molecules in the buffer solution for catalyzing the cellulose hydrolysis and in turn the glucose yield. ,, It is thus speculated that lignin might exhibit a higher adhesion strength with cellulase than that with cellulose …”
Section: Resultssupporting
confidence: 69%
“…The negative effects of lignin on enzymatic hydrolysis have been comprehensively reviewed and discussed by many researchers. , We also confirmed the inhibition of lignin (milled bamboo lignin, MBL) to the enzymatic conversion (EC) of typical microcrystalline cellulose (Avicel) (Figure S3). Based on macroscopic adsorption experiments, numerous studies had found that competitive adsorption of cellulase with lignin was more superior to that with cellulose in a coexisting buffer system, which significantly reduced the amount of effective cellulase molecules in the buffer solution for catalyzing the cellulose hydrolysis and in turn the glucose yield. ,, It is thus speculated that lignin might exhibit a higher adhesion strength with cellulase than that with cellulose …”
Section: Resultssupporting
confidence: 69%
“…4 c). In addition, the lignin coverage on fiber surface of EOS + 2N substrate was also quantitatively determined by O/C ratio of XPS analysis [ 45 ], which was even higher than that on EOS substrate surface (Table 4 ). Results confirmed the aggravated exterior lignin coverage caused by 2-naphthol addition in acid EOS treatment, which in turn proved the greater fluidity of the less repolymerized lignin that modified by 2-naphthol.…”
Section: Resultsmentioning
confidence: 99%
“…Enzymatic hydrolysis of the delignified substrate was performed as specified above. The gap between enzymatic hydrolysis of delignified and non-delignified EOS substrates indicated the total lignin inhibition on cellulose hydrolysis, including unproductive binding effect and surface barrier effect [ 45 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, the hydrolysate was transferred to a screw-capped tube and boiled for 5 min to stop the enzymatic reaction. The obtained solution was analyzed for the contents of the released reducing sugars using HPLC and the degree of saccharification (DS) , using eq . DS = c · v · f 1 m · f 2 where c denotes the concentration of sugar in the hydrolysate (mg mL –1 ), v represents the volume of hydrolysate (mL), f 1 indicates the factor (0.90 for glucose and 0.88 for xylose) used to convert polysaccharide to monosaccharide during saccharification, m refers to the initial weight of the dry substrate (mg), and f 2 denotes the factor for the content of carbohydrate in the substrate, which was cellulose and hemicellulose for DS calculations of glucose and xylose (mg mg –1 ), respectively.…”
Section: Methodsmentioning
confidence: 99%